Primary Pulmonary Ewing’s Sarcoma - Rehana, Kausar; Shafiq, Muhammad Mudassir (International Journal of Pathology, 2018)
Ewing sarcoma is a malignant small round blue cell peripheral primitive neuroectodermal tumor (PNET). Its most common location is flat bones including pelvic bones, ribs and clavicle. It does however occasionally occur in femur and humerus. Rarely Ewing’s sarcoma occurs in soft tissues known as Extraskeletal Ewing’s sarcoma. A large Ewing sarcoma arising in the chest from rib or vertebral column is known as a skin tumor! We report a case of a 10-year-old girl who presented with right sided lung mass. Radiology, histopathology and immunohistochemistry confirmed the diagnosis of Ewing’s sarcoma. Our case highlights the fact that Ewings sarcoma/PNET should be considered in differential diagnosis of patients presenting with lung mass.